Parental Aspirations for Distance Learning during the Pandemic - Leonardi, Tino; Surjaningrum, Endang R; Fajrianthi, Fajrianthi (Journal Of Teaching And Learning In Elementary Education, 2024)
The research aims to describe parents' aspirations of distance learning for children during the pandemic. Aspiration shows an individual's hope to achieve something expected. Aspirations can include theoretical differences between idealistic and realistic levels of aspiration. The aspirations are parents' hopes regarding appropriate learning for their children. These aspirations include learning methods, processes, and behavior in children. The informants are parents of elementary or middle school students who learn through distance learning with consideration that students at the level still need more parental support. The research uses descriptive content analysis methods using information from parents about school learning during the pandemic in online news media between March and November 2020. The search yielded 38 relevant online news articles. Findings include parents hoping that their children will learn face-to-face at school because online learning is considered less effective. Three types of aspirations were obtained: considering distance learning less effective because schools are not ready to carry out online learning, also considering less effective because parents are unable to accompany them and accept distance learning by accompanying children to learn Working status seems less influential because some parents encourage face-to-face meetings and some want to accompany their children to study. This shows that distance learning requires the role of schools and parents to be beneficial for children.